1996
DOI: 10.1121/1.417360
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive temperature estimation in tissue via ultrasound echo-shifts. Part II. Invitro study

Abstract: Time shifts in echo signals returning from a heated volume of tissue correlate well with the temperature changes. In this study the relationship between these time shifts (or delays) and the tissue temperature was investigated in excised muscle tissue (turkey breast) as a possible dosimetric method. Heat was induced by the repeated activation of a sharply focused high-intensity ultrasound beam. Pulse echoes were sent and received with a confocal diagnostic transducer during the brief periods when the high-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 6 publications
2
106
0
Order By: Relevance
“…In particular, papers by Sun and Ying [23], Seip, Simon, Ebbini and coworkers [54][55][56], Maass-Moreno, Damianou and coworkers [57][58][59] and this group [29,60,61] have reported the changes in received ultrasonic signals due to changes in ultrasonic tissue characteristics with temperature. These changes have been investigated both theoretically and in vitro with an eye towards using these signals for non-invasive monitoring of thermal therapy.…”
Section: Ultrasonic Measurement Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, papers by Sun and Ying [23], Seip, Simon, Ebbini and coworkers [54][55][56], Maass-Moreno, Damianou and coworkers [57][58][59] and this group [29,60,61] have reported the changes in received ultrasonic signals due to changes in ultrasonic tissue characteristics with temperature. These changes have been investigated both theoretically and in vitro with an eye towards using these signals for non-invasive monitoring of thermal therapy.…”
Section: Ultrasonic Measurement Of Temperaturementioning
confidence: 99%
“…Most of these efforts have been geared towards high intensity focused ultrasound (HIFU) therapy, which typically heats small volumes of tissue to above 60 C. In investigations by Ebbini and coworkers, tracking echo shifts from scattering volumes was shown to be promising, as was the work of other investigators looking at the echo shifts [56]. Maass-Moreno and coworkers investigated the ability to predict temperature in HIFU therapy from echo shifts in turkey breast muscle [57,58]. They found that results were consistent with their theoretical predictions.…”
Section: Echo Shiftsmentioning
confidence: 99%
“…As the temperature increases in soft tissue, the tissue expands and the ultrasonic propagation speed changes, introducing physical and apparent shifts in scatterer position, respectively [1 -7]. The latter is dominant over a wide range of operating conditions near body temperature (nominally 378C) [8,9]. The local temporal gradient of scatterer shift, often called the thermal strain, is directly related to tissue composition and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter estimation technique is based on visualizing the spatiotemporal variation of temperature induced strain (Miller et al 2002(Miller et al , 2004 estimated from the raw ultrasound backscatter data after a short focused ultrasound heating pulse is applied at subablative intensities. The temperature induced strain is caused by changes in the local sound speed of the medium and thermal expansion (Maass-Moreno et al 1996;Simon et al 1998;Varghese et al 2002). The maximum induced temperature rise is less than 10°C to avoid any permanent changes in tissue.…”
Section: Introductionmentioning
confidence: 99%